PESCI VOLANTI DEL GENERE THORACOPTERUS NEL NORICO LOMBARDO. NOTA PRELIMINARE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A biplane fossil flying fish, Thoracopterus magnificus sp. n. is described from the Norian of Lombardy. The main differences with the Carnian species Thoracopterus niederristi are the nakeness of the body and the remarkable shortness of the sopraorbital sensory canal in the frontal. Sometimes fusion on the skull roofing bones can take place. Large otholites are present and are here described and figured for the first time 111 this group. Dentition is powerful so that Thoracopterus magnificus sp. n. is regarded as a predator fish. The paired fins are very large and their proximal segments widely overlap ensure a good tightness even when the fins, during the flight, are completely open. The caudal fin is almost homocercal and the ventral lobe is more expanded than the dorsal one. Size ranges from 3—4 cm to 13.5 cm in standard length.
Keywords: Perleididae (Actinopterygii); Flying fishes; New taxon; Thoracopterus magnificus; Otholites; Upper Triassic; Lombardy; N. Italy.